Chapter Deideia / Dell'idea - Correia, António (Studi di Traduzione Letteraria Lusofona, 2023)
Macao amore mio and Dell'idea are the Italian translations of the two Portuguese colletions of sonnets of António Correia: Deideia and Amagao meu amor. These literary works have been translated for the first time in Italian language by Michela Graziani in this volume. The Italian translation provides the Italian reader to appreciate the poetry style of António Correia and to approach this fascinating Portuguese author of our contemporary age.